In vitro prospective effects of various traditional herbal coffees consumed in Anatolia linked to neurodegeneration - Sekeroglu, Nazim; Senol, F. Sezer; Orhan, Ilkay Erdogan; Gulpinar, A. Rifat; Kartal, Murat; Sener, Bilge (Elsevier, 2012)
Various herbal coffee varieties are consumed traditionally in Turkey. In the current study, the ethanol extracts of the coffee and seed samples obtained from Gundelia tournefortii (tumble thistle), Nigella sativa (black cumin), Phoenix dactylifera (date), and Ceratonia siliqua (carob) as well as a sample of instant coffee (Nescafe (R), green blend) were tested against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and tyrosinase, the enzymes connected to neurodegeneration. Since oxidative stress is strongly associated with neurodegeneration, antioxidant activity of the extracts was also determined. Antioxidant activity of the extracts was measured using anti-radical and metal-related methods. Total phenol and flavonoid contents were calculated using Folin-Ciocalteau's and AlCl3 reagents, respectively. Fatty acid compositions of the seed oils of tumble thistle and black seed were analyzed by GC-MS. Our results showed that the date sample exerted the highest AChE and BChE inhibition at 300 mu g mL(-1) (52.96% and 83.22%, respectively). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Traditional coffees; Cholinesterase inhibition; Antioxidant activity; Fatty oil